Peran Optimalisasi Pemberdayaan Nelayan Terhadap Peningkatan Usaha (Studi pada KUB-KUB Nelayan di Kabupaten Pati) - Yusuf Hardjono; Muh Sofi'i; Novita Setianti (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2017)
Pati is a rich regency with fisheries and oceanic resources . Most of the population live in north coast and their life depend on fishery resource.In reality most of the coast people live under the poverty line .To overcome the poperty of coast society. Indonesia government has carried out various programs society inpowerment seciety. One of the program is inpowerment fish effort for villagers called “ Pemberdayaan Usaha Mina Pedesaan “ ( PUMP ) which is developed to be national program. The purpose of “ PUMP “ is welfare raising for coast seciety by fiherman economic assosiation,called “ Kelompok Usaha Bersama “ ( KUB ) that means effort cooperation group.The purpose of the research is ( 1 ) to analyze commitment influence to fisherman inpowerment, (2 ) to analyze competence influence to fisherman inpowerment , (3 ) to analyze Commitment in fluence to effort raising, (4 ) to analyze Competence influence to effort raising ; ( 5 ) to analyze the influence of fisherman inpowerment to effort raising. This research uses sample method by case study approach.The subjects of research is 133 fisherman respondents as “ KUB “ members in district under oceanic and fishery service ( “ Dinas Kelautan dan Perikanan “ ) in Pati regency. The soffwere to analyze data is SPSS 19. The menthod data procesor is analysis similarity dauble regression linear gradually used for reaserch the influence of variable free commetment,comptence about bounded variable that is variable of fisherman inpowerment and effort raising. The research result show that commitment,fishreman competence member of “ KUB “ influential positive and sgnificant about fiherman inpowerment and effort raising.